Конструктивные особенности планетарных гидромоторов серии PRG - Панченко, Анатолий Иванович; Волошина, Анжела Анатольевна; Панченко, Игорь Анатольевич (НТУ "ХПИ", 2018)
Представлены конструктивные особенности планетарных гидромоторов серии PRG. Обоснованы схемы взаимодействия элементов вытеснительной и распределительной систем. Предложен механизм, компенсирующий планетарное движение вытеснителей, аналогичный работе планетарного редуктора. Рассмотрено движение рабочей жидкости в распределительной системе. Обосновано использование элементов системы распределения рабочей жидкости в качестве торцевого уплотнения выходного конца вала планетарного гидромотора.

The paper presents design features of the planetary hydraulic motors of PRG series as well as their displacement and distribution systems. Four standard unified motor series (PRG-33, PRG-22, PRG-11 and PRG-8) have been developed. The hydraulic motors have power of 33, 22, 11 and 8 kW. Rotational speed, which the motors provide, ranges from 1420 to 75 rpm according to the power change. The hydraulic motors of each unified series have the same connecting dimensions and input characteristics and differ in linear dimensions, mass and output characteristics according to the working volume change from 35 to 1600 cm³. The unification level of the motors in each series is up to 85 %. The schemes of interaction between elements of the displacement and distribution systems are justified. A mechanism, which compensates the planetary motion of displacers, is proposed. Its work is similar to the work of the planetary reducer. The movement of working fluid in the distribution system has been considered. The use of the elements of the working fluid distribution system as a face seal of an output end for PRG motor shaft is justified.
Design features of the planetary hydraulic motors of PRG series
Keywords: вытеснительная система; компенсирующий механизм; распределительная система; золотник; уплотнение выходного вала; рабочая жидкость; displacement system; compensating mechanism; distribution system; output shaft seal; working fluid